The Baby Watch Book Improve Mothers' Knowledge About Infant Development - Baiq Eka Putri Saudia; Widya Safitarini; Mira Utami Ningsih; Muhammad Hasbi (Jurnal Keperawatan Terpadu (Integrated Nursing Journal), 2022)
The growth and development of children in Indonesia still needs serious attention. The rate of growth and development delays is still quite high. Providing health education by health workers is an effective way to deliver valid, updated and evidence-based information. The baby watch book can be used as an educational tool for the baby's mother, specifically designed to increase the knowledge and skills of the parents. This study was a pre-experiment study with a one-group pretest-posttest design. The sample was 30 mothers of infants at the Karang Taliwang Health Center. Data analysis used was the Wilcoxon Signed Rank Test. The results show that the majority of respondents were aged 20–35 years (80%), graduated from senior high school education (43.3%), working as a housewife (86.7%), and their main sources of information was health workers (23.3%). Before the intervention, most of the respondent has poor knowledge (50%). After given the intervention, there was an increase in their knowledge; there were 97% respondent have a good knowledge. Wilcoxon sign ranked test showed p-value 0.000 (p<0.05). This means that there was a significant effect of health education using baby watch book on mothers' knowledge about the development of babies aged 3 to 6 months.